PEMBERDAYAAN MASYARAKAT MELALUI PENDIDIKAN NONFORMAL PADA PENYANDANG MASALAH KESEJAHTERAAN SOSIAL (PMKS) - Aina Rahmatunisa Farhati; Azwia Az-Zahrah; Elsa Salsabillah; Dewi Utari; Novalia Rahmah; Siti Yhunis Arum (Lembaran Masyarakat: Jurnal Pengembangan Masyarakat Islam, 2020)
Improving high character in children is very important to start as early as possible. The characters that have instilled from an early age will become their personalities, as they get older. This article aims to identify and analysis the process of empowermet through informal education to children with social welfare problems (Indonesian: Penyandang Masalah Kesejahteraan Sosial/PMKS). This study used Participatory Need Assessment (PNA). The result shown that the children with PMKS condition who are experiencing social, moral, and material barriers that are included in these categories, such as the poor, street children, beggars, scavengers and others. They are a group that needs to be empowered, that aims to form an honest, disciplined and responsible character for PMKS children through the Socialization Program for improving learning motivation and tahfidzul Qur'an.